Carboxymethyl chitosan as a polyampholyte mediating intrafibrillar mineralization of collagen via collagen/ACP self-assembly. Issue 9 (September 2019) - Lin, Mingli; Liu, Huanhuan; Deng, Jingjing; An, Ran; Shen, Minjuan; Li, Yanqiu; Zhang, Xu
Abstract: The significant role of the polyelectrolytic nature of non-collagenous proteins (NCPs) in regulating the in vivo mineralization of collagen provides important insights for scientists searching for analogues of NCPs to achieve in vitro collagen mineralization. Polyampholyte carboxymethyl chitosan (CMC) has both carboxyl and amino groups, which allows it to act as a cationic or anionic polyelectrolyte below or above its isoelectric point (IP), respectively. In this study, CMC was employed as the analogue of NCPs to stabilize amorphous calcium phosphate (ACP) under acidic conditions (pH < 3.5) via the formation of CMC/ACP nanocomplexes. In the presence of both ACP nanoparticles and acid collagen molecules, ACP nanoparticles could be integrated into collagen fibrils during the process of collagen self-assembly and achieve intrafibrillar mineralization of collagen in vitro (i.e., synchronous self-assembly/mineralization (SSM) of collagen). This mode of mineralization is different from established mechanisms in which mineralization follows the self-assembly (MFS) of collagen. Thus, SSM provides a new strategy for developing materials from mineralized collagen scaffolds.